2019
DOI: 10.1111/jcmm.14736
|View full text |Cite
|
Sign up to set email alerts
|

CircRhoC promotes tumorigenicity and progression in ovarian cancer by functioning as a miR‐302e sponge to positively regulate VEGFA

Abstract: Ovarian cancer is a leading cause of deaths due to gynaecological malignancy. While endogenous non‐coding circular RNAs (circRNAs) in cancer have attracted attention, their roles in ovarian cancer are not known. We used qRT‐PCR to quantify expression of circRhoC in ovarian cancer tissues and normal tissues. The effects of overexpressing or destruction of circRhoC on the phenotype of ovarian cancer cells were assessed both in vitro and in vivo. Dual‐luciferase reporter assay assesses the microRNA sponge functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 35 publications
(55 reference statements)
0
26
0
Order By: Relevance
“…Suppression of circRhoC with shRNA significantly attenuated cell migration and invasion in vitro, and inhibited the intraperitoneal dissemination of OC cells in vivo [140]. By performing mechanistic analysis, the same study indicated that circRhoC can serve as a sponge for miR-302e to upregulate the expression of VEGF-A, which potentially promotes OC angiogenesis and metastasis [140].…”
Section: Circrnas Promotes Angiogenesis In Ocmentioning
confidence: 97%
See 2 more Smart Citations
“…Suppression of circRhoC with shRNA significantly attenuated cell migration and invasion in vitro, and inhibited the intraperitoneal dissemination of OC cells in vivo [140]. By performing mechanistic analysis, the same study indicated that circRhoC can serve as a sponge for miR-302e to upregulate the expression of VEGF-A, which potentially promotes OC angiogenesis and metastasis [140].…”
Section: Circrnas Promotes Angiogenesis In Ocmentioning
confidence: 97%
“…Vascular endothelial growth factor (VEGF-A) has a prominent role in tumor angiogenesis [139]. CircRhoC, a circRNA derived from the RhoC mRNA, was overexpressed in OC tissues relative to normal ovarian tissues, and higher circRhoC expression was detected in advanced-stage tumors compared with early-stage tumors [140]. Suppression of circRhoC with shRNA significantly attenuated cell migration and invasion in vitro, and inhibited the intraperitoneal dissemination of OC cells in vivo [140].…”
Section: Circrnas Promotes Angiogenesis In Ocmentioning
confidence: 99%
See 1 more Smart Citation
“…microRNAs (miRNAs) are a group of small noncoding RNAs which could regulate the post‐transcription expression level of their target genes 11,12 . Numerous studies have reported the close correlation between the aberrant expression of certain miRNAs and cancer progression 13,14 . For instance, miR‐193a‐3p was reported to regulate cisplatin resistance in CD44(+) gastric cancer cells 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our previous research reported that circRhoC functions not only as a miR-302e sponge to positively regulate VEGFA protein expression, but may also directly bind and modulate VEGFA expression to promote ovarian cancer development. [22]. Using bioinformatic analysis, we found that circNOLC1 could also bind with proteins such as ESRP1.…”
Section: Discussionmentioning
confidence: 95%